1997
DOI: 10.1152/ajpcell.1997.272.4.c1271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic hypoxia on K+ channels: regulation in human pulmonary vascular smooth muscle cells

Abstract: We investigated the effects of chronic hypoxia on the major outward K+ currents in early cultured human main pulmonary arterial smooth muscle cells (HPSMC). Unitary currents were measured from inside-out, outside-out, and cell-attached patches of HPSMC. Chronic hypoxia depolarized resting membrane potential (Em) and reduced the activity of a charybdotoxin (CTX)- and iberiotoxin-sensitive, Ca2+-dependent K+ channel (KCa). The 4-aminopyridine-sensitive and CTX-insensitive channel or the delayed rectifier K+ chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 4 publications
3
34
0
1
Order By: Relevance
“…In this situation, KCa channel opening repolarises the cell membrane and, thus, functions as a servomechanism limiting the extent of depolarisation and consequent Ca influx, vasoconstriction, and proliferation [10,12,13]. Although pulmonary vascular smooth muscle depolarisation and increased [Ca 2z ] i are present in pulmonary hypertension [28][29][30][31][32][33], and, thus, KCa channel activity would be expected to rise, it has actually been repeatedly shown to be reduced [31,33], possibly due to downregulation of the channel protein expression. The cause and mechanism of this KCa channel downregulation is unknown, but it probably contributes to the sustained depolarisation and increased [Ca 2z ] i of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, KCa channel opening repolarises the cell membrane and, thus, functions as a servomechanism limiting the extent of depolarisation and consequent Ca influx, vasoconstriction, and proliferation [10,12,13]. Although pulmonary vascular smooth muscle depolarisation and increased [Ca 2z ] i are present in pulmonary hypertension [28][29][30][31][32][33], and, thus, KCa channel activity would be expected to rise, it has actually been repeatedly shown to be reduced [31,33], possibly due to downregulation of the channel protein expression. The cause and mechanism of this KCa channel downregulation is unknown, but it probably contributes to the sustained depolarisation and increased [Ca 2z ] i of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of DHEA on 5-HT-induced contraction may involve an effect on a signaling pathway that mobilizes intracellular calcium (9) given that we have previously demonstrated that CH modifies resting cytosolic calcium concentration and agonist-induced contraction in PASMCs from the adult rat (28). The effect of DHEA on KCl-induced contraction may involve ionic conductance because CH depolarizes the cell membrane and downregulates potassium channels in adult rat and human PASMCs (29,30). Likewise, in the present study, we have shown that CH decreases potassium currents in PASMCs from juvenile rats and that this effect is prevented following DHEA treatment.…”
Section: Dhea Prevents Pulmonary Hypertensionmentioning
confidence: 99%
“…Previously, hypoxia has been shown to alter potassium channel pathways [216][217][218], and potassium channels are involved in oxygen sensing and in regulation of apoptosis [219]. Interestingly, exocytosis of potassium voltage-gated channels to the plasma membrane is known to be regulated by Rab 11, a relative of the putative Hsp90-binding Rab proteins that we identified ( Figure 35) [215].…”
Section: In Addition Putative Hsp90-binding Proteins Identified By Lmentioning
confidence: 66%
“…These potassium channels may also be regulated by the idenfied calcium channels that is involved in endocytosis. Indeed, some potassium channels depend on calcium channels for activation [218,220]. In addition, Dynein binding has been shown to downregulate potassium channel expression at the plasma membrane following channel internalization [221].…”
Section: In Addition Putative Hsp90-binding Proteins Identified By Lmentioning
confidence: 99%